Long‐term survival after surgical resection for huge hepatocellular carcinoma: Comparison with transarterial chemoembolization after propensity score matching. Issue 5 (May 2014) - Min, Yang Won; Lee, Jun Hee; Gwak, Geum‐Youn; Paik, Yong Han; Lee, Joon Hyoek; Rhee, Poong‐Lyul; Koh, Kwang Cheol; Paik, Seung Woon; Yoo, Byung Chul; Choi, Moon Seok
Abstract Background and Aims Surgical resection (SR) and transarterial chemoembolization (TACE) have been commonly applied for patients with huge hepatocellular carcinoma (HCC). However, optimal treatment has not been established. Methods Between 2000 and 2009, 267 patients with huge HCC (≥ 10 cm) underwent TACE and 84 underwent SR as the first treatment. Propensity score matching generated a matched cohort composed of 152 patients. We investigated overall survival and possible prognostic factors. Results At baseline, the surgery group showed a tendency to have solitary tumor (72.6% vs 39.3%, P < 0.001), less vessel invasion (29.8% vs 51.3%, P < 0.001), and unilobar tumor extent (77.4% vs 50.9%, P < 0.001) than TACE group. During median follow up of 10 months (range: 0–103), the surgery group showed higher 1‐, 3‐, and 5‐year overall survival rates than TACE group (73.8%, 54.8%, and 39.8% vs 37.8%, 16.3%, and 9.7%, respectively, P < 0.001). In the propensity score‐matched cohort, baseline characteristics did not differ between the two groups. Surgery group showed higher 1‐, 2‐, and 3‐year overall survival rates than TACE group (69.7%, 58.6%, and 51.7% vs 40.2%, 33.9%, and 18.5%, respectively, P < 0.001) during median follow up of 14.5 months (range: 0–103). Multivariate analysis revealed that male (HR 1.90; 95% CI, 1.01–3.58; P = 0.048), albumin (HR 0.54; 95% CI, 0.34–0.85; P = 0.008), ascites (HR 1.77; 95% CI, 1.02–3.08; P = 0.044), and SR (HR 0.44; 95% CI, 0.28–0.70; P = 0.001) were the independent prognostic factors associated with survival. Conclusion Comparing survival after SR and TACE, we showed that SR would be associated with better outcomes than TACE as the first treatment of huge HCC.